Main approaches and methods of geoecological mapping the territory of Western Kazakhstan (Journal of Geography and Environmental Management, 2018)
The deterioration of the environment in many regions, the modification and degradation of naturalgeosystems and the conditions of life support for the population lead to a real ecological danger with far-reaching and unpredictable consequences for the existence of mankind. More and more popular andpromising are studies on assessing the state of the environment and determining the degree of favorableor unfavorable conditions in specific areas for the population.Interaction between society and the environment, which occurs in various zonal-natural and socioeconomicconditions, at the level of specific modern geosystems, i.e. in certain areas, makes us considerresearch as complex ecosystems represented by various natural-anthropogenic complexes, the core ofwhich is the person himself. In such ecosystems, a person lives not only in the natural, but also in thetechnogenic, economic, social, ethno-cultural and many other environments that acquire territorial expression.All these environments surrounding the human are interrelated, differentiated, integrated intovarious structures and form a common geoecosociosystem, the functioning of which is determined bythe assessment of its state.Deterioration of the state of natural environment and ensuring environmental safety require creation ofa visual image of a new environmental reality. This task corresponds most closely to the cartographic form,which adequately reflects the ecological situation. Ecological maps have a special role in the implementationof environmental control, organization of monitoring, implementation of environmental measures,management of natural activities. The mapping of anthropogenic human influence on the environment isa complex task, which is primarily due to the multiplicity of characteristics that require systematization. Inthis respect, complex ecological mapping is comparable not with any particular thematic area (geological,soil, socio-economic and other mapping), but with thematic cartography as a whole.One of such regions for mapping is the territory of Western Kazakhstan. The purpose of mapping isto analyze the ecological situation and its zoning, i.e. the identification of spatial and temporal variabilityof environmental factors affecting the state of ecosystems. The mapping of ecological zoning shouldbe considered as the logical completion of an independent study – an eco-geographical analysis of anyterritory aimed at determining those conditions and properties that characterize the environment surroundinga person.Ecological assessment and mapping of the territory aim at the practice of improving the ecologicaland economic balance of the territory, its environmentally safe and harmonious development, abandoningthe destructive industrial and consumer ideology, and radically changing the system of priorities andvalues in the sphere of nature management.